High Tongue Position is a Risk Factor for Upper Airway Concentric Collapse in Obstructive Sleep Apnea: Observation Through Sleep Endoscopy - Zhao C (Nature and Science of Sleep, 2020)
Chen Zhao,1,2 Alonço Viana,2– 4 Yifei Ma,5 Robson Capasso2 1Department of Otorhinolaryngology, The First Affiliated Hospital of China Medical University, Shenyang, Liaoning, People’s Republic of China; 2Division of Sleep Surgery, Department of Otolaryngology- Head & Neck Surgery, Stanford University Medical Center, Stanford, CA, USA; 3Graduate Program of Neurology, Rio de Janeiro State Federal University (UNIRIO), Rio de Janeiro, Brazil; 4Department of Otorhinolaryngology, Marcílio Dias Naval Hospital, Rio de Janeiro, Brazil; 5Department of Otolaryngology- Head & Neck Surgery, Stanford University Medical Center, Stanford, CA, USACorrespondence: Chen ZhaoDepartment of Otorhinolaryngology, The First Affiliated Hospital of China Medical University, No. 155, North Nanjing Street, Heping District, Shenyang, Liaoning 110001, People’s Republic of ChinaTel +86 13998856576Fax +86 02483282997Email zhaochen@cmu.edu.cnPurpose: Identification of upper airway (UA) obstruction based on pharyngeal factors is important for obstructive sleep apnea (OSA) evaluation. This study is to assess the association between UA collapse characteristics and Friedman tongue position (FTP) in patients with OSA through drug-induced sleep endoscopy (DISE).Patients and Methods: Retrospective study in individuals with OSA who were intolerant to continuous positive airway pressure (CPAP) treatment, submitted to DISE between June 1, 2013, and July 31, 2017. All subjects were classified as having an FTP grade of I to IV, and the velum, oropharynx, tongue base, epiglottis (VOTE) classification was used to analyze the DISE findings. UA collapse characteristics by DISE and FTP grading were compared between groups. The associations between specific DISE findings and FTP were analyzed.Results: In total, 205 patients were assessed. A positive and significant correlation was identified between the presence of retropalatal complete concentric collapse (CCC) and FTP grade, according to the following distributions: I, 17.4%; II, 22.9%; III, 33.7%; and IV, 48.7% (P = 0.014). A logistic regression model revealed that CCC was associated with FTP grade IV. After adjusting for age, sex, body mass index (BMI), and tonsil size (TS), the grade IV individuals had a 4.4-fold higher risk of having CCC than grade I individuals (P = 0.026). Multiple collapse sites and palatopharyngeal or combined (palatopharyngeal and hypopharyngeal) collapse were more prevalent in grade IV individuals.Conclusion: OSA patients intolerant to CPAP have a strong positive correlation between the FTP grade and presence of retropalatal CCC. FTP grade IV is an independent risk factor for velum-CCC, controlling for sex, age, BMI, and TS grade.Keywords: drug-induced sedation endoscopy, sleep endoscopy, obstructive sleep apnea, tongue position, upper airway collapse, complete concentric collapse